Glasbenogledališki opus Darijana Božiča v kontekstu slovenske glasbenogledališke scene - izmik v literarno-dramsko v opreki z željo po institucionalnem - Pompe, Gregor (Amfiteater (Ljubljana), 2023)
Among Slovenian modernist composers, Darijan Božič dedicated the largest part of his work to musical theatre. The genre classifications of his works show that the composer constantly searched for a new form of musical theatre. It would appear that he finally settled on a medium that could almost be designated as a “radio play”, with an emphasis usually on the spoken word, accompanied by occasional interventions of instrumental music. Over time, these interventions appeared to lose their modernist edge (harmonic clusters) and approach postmodernism by juxtaposing diverse elements. Thus, a characteristic of Božic’s works is their double imbalance: the language strongly dominates the music, while at the same time, the composer’s desire to implement avant-garde theatrical procedures in an institutional opera house seems unusual.
Keywords: 20th-century music; Božič, Darijan; glasba 20. st.; glasbeno gledališče; instrumental theatre; instrumentalno gledališče; modernism; modernizem; musical theatre; scenske kompozicije; Slovenian opera; slovenska opera; stage compositions